1967
DOI: 10.1002/jsfa.2740180809
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on decontamination of mixed feeds by radicidation and by pelletisation

Abstract: Feed components contaminated with Salmonella act as vehicles in the transmission of these bacteria to animals and hence to meat and poultry. Sanitary improvements in processing, bagging and storage do not always effectively reduce Salmonella contamination rates and therefore ingredients or mixed feed should be decontaminated at the end of processing.Enumeration of Enterobacteriaceae was used to assay the decontamination effect of pelletisation of mixed feed. A working temperature over 80" usually reduced the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Generally the mixed ingredients are heated by direct contact of the meal with steam before being forced through a die to form the pellets. Pelleting has been shown to bring about significant reductions in the numbers of Enterobacteriaceae and Salmonellae contaminating the mixed ingredients (Mossel, van Schothorst & Kampelmacher, 1967;Stott, Hodgson & Chaney, J 975). The reduction in the viable bacterial count achieved by pelleting may be sufficient to satisfy microbiological limits suggested for the numbers and types of contaminants that can be tolerated on diets intended for conventional laboratory stock (Coates, O'Donoghue, Payne & Ward, 1969;Clarke et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Generally the mixed ingredients are heated by direct contact of the meal with steam before being forced through a die to form the pellets. Pelleting has been shown to bring about significant reductions in the numbers of Enterobacteriaceae and Salmonellae contaminating the mixed ingredients (Mossel, van Schothorst & Kampelmacher, 1967;Stott, Hodgson & Chaney, J 975). The reduction in the viable bacterial count achieved by pelleting may be sufficient to satisfy microbiological limits suggested for the numbers and types of contaminants that can be tolerated on diets intended for conventional laboratory stock (Coates, O'Donoghue, Payne & Ward, 1969;Clarke et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Heat treatment has traditionally been considered the simplest and most cost effective method of decontaminating feed (Saulmon, 1966;Nape and Murphy, 1971;Williams, 1981). Many studies have demonstrated the potential of heat to reduce microbial contamination (Mossel et al, 1967;Stott et al, 1975;Jones et al, 1991;Veldman et al, 1995). The effectiveness of heat treatment is considerably influenced by the constituents of the feed (especially fats) (Doyle and Mazzotta, 2000;Juneja and Eblen, 2000), available water levels (Liu et al, 1969;Farkas, 2001), level and homogeneity of contamination, the temperature profile achieved through the batch of feed and individual feed particles and the minimum treatment period (Ricke, 2005).…”
Section: Heat Treatment Of Feedingstuffsmentioning
confidence: 99%
“…In the former, doses of ionizing radiation are assessed that will result in the same degree of reduction of cfu counts of Salmonella or Enterobacteriaceae as is achieved in a comparable, conventional mode of processing, particularly a thermal decontamination treatment. This mode of assessing required MPED's of radiation has been successfully applied in studies on the decontamination of mixed feed, where steam pelletisation is such a similar, conventional process (Mossel et al 1967). It is not very feasible for dose assessment of radicidation of fresh meats and poultry, where no analogous thermal mode of processing is available for comparison.…”
Section: Estlmation Of Most Probable Effective Dose (Mped) Under Pracmentioning
confidence: 99%